INDIGENOUS PEOPLE - Kadankavil, Thomas (Journal of Dharma, 1999)
Today dalitism is a much spoken word in the Indian subcontinent. Many of the developing countries are now victims of capitalism, which has established an inhuman society by constantly pushing the disempowered poor out of the development circle to a sub-human social existence. Social classification of Indian society into castes also aggravates the plight of the downtrodden or broken, who are here designated by the Indian term dalits. It is fashionable to use the term 'subaltern' among academics to refer to this section of the people.